Alfabetização científica por meio da literatura de Júlio Verne - Lopes, Daisy Alves de Souza (2023)
The work in question addresses a possible approximation between science fiction literature and the Natural Sciences as a means to assist in the scientific literacy of students in the final years of Elementary School. The work is based on a literature review and addresses Jules Verne's work, Journey to the Center of the Earth (1864), as a primary source of research, an example of how literature can approach science, obviously respecting the characteristics specific to each of these areas, and be used creatively in the classroom and, above all, as a scientific literacy tool. The philosophers Edgar Morin, Michel Serres, Paulo Freire, Humberto Maturana, the neuroscientist Maryane Wolf, the researcher Áttico Chassot, and other authors who address the theory of knowledge, acquisition of reading skills and the teaching of science, were the secondary sources that supported this research. Scientific literature is often marked by complex nomenclatures and conceptual definitions, which can make it difficult for students to understand the world and natural phenomena, which is one of the challenges faced in science teaching. Another approach presented in this work is the concept of Science and its purpose in today's society. Science is presented as a way of explaining the world that surrounds us, and the teaching of Science is fundamental to help understanding how this world works, and goes beyond, helping to develop important skills in society, such as critical thinking and problem solving. However, for Science teaching to become more accessible, and to be careful to avoid trivializing concepts and contents, it is essential that students acquire the habit of reading. In this sense, the work highlights that the practice of reading is fundamental for the scientific training of students and also in cognitive and social areas, both in the school environment and outside it. However, research shows that Brazil invests little in this area, generating low proficiency in reading and science on the part of students, according to 2018 data from the Program for International Student Assessment, or PISA. The research proposal aimed to analyze how science fiction texts can contribute to the scientific literacy of students in the final years of Elementary School. Throughout the study, it was noted that science fiction literature can be a valuable tool to explore scientific and also philosophical and social issues, in addition to attracting students to literature and science.